Numerical study towards the use of a SH wave ultrasonic-based strategy for crack detection in concrete structures - Godinho, L. (2014)
The cost of rehabilitation works increases exponentially with time. Therefore, the development of on-site non-destructive tests (NDTs) for early detection of damage in concrete structures is an extremely important goal. However, in spite of the recent new technological developments, current assessment techniques are still based on visual inspections and are therefore only suitable for mapping major damages. An ultrasound-based procedure aiming to detect cracking at an early stage using propagation of ultrasonic waves is herein analysed. Two advanced numerical models were applied to simulate, first, the process of crack propagation and, next, the propagation of ultrasonic waves in a progressively damaged structure. Results are promising and enforce the feasibility of developing ultrasonic equipment for on-site application. Thus, future developments include an experimental validation of the present study.